MANAJEMEN LABA MENGGUNAKAN CLASSIFICATION SHIFTING MELALUI DISCONTINUED OPERATIONS - Taniadji, Vanessa; Shanti, Shanti; Dwijayanti, S, Patricia Febrina (Widya Mandala Surabaya Catholic University, 2014)
Earnings management using classification shifting is done by changing the classification of an item in the income statement. Classification shifting does not change the company’s net profit, but the core earnings of that year will be reported too high. Earn-ings management using classification shifting may miss understand the users of financial statements, because investors are more attend to core earnings than net income. The purpose of this research is to prove whether the managers of manufacturing compa-nies in Indonesia do earnings management using classification shifting trough discontinued operations. This research is quantita-tive descriptive research with the object of this research is manufacturing companies listed on the Indonesia Stock Exchange from 1996 to 2012. The sample of this research is manufacturing companies that reported discontinued operations account in 1998 until 2011, because this research need 2 lag data and 1 lead data. Sampling in this research is purposive sampling. Source of the data in this research is the company’s financial statement and Indonesian Capital Market Directory. Data analysis techniques which is used in this research is multiple linear regression analysis. The result of this research show that the reporting of discontinued operations account doesn’t have significantly effect to core earnings. Based on that result, it can be concluded that managers of manufacturing companies in Indonesia doesn’t proven to do earnings management using classification shifting trough discontin-ued operations.